EL LAPSUS CALAMI EN TEXTOS MEDIEVALES. ANÁLISIS DESCRIPTIVO - Espinosa Elorza, Rosa María (Revista de Investigación Lingüística, 1997)
The different types of graphic errors in Castilian texts of the Middle Age have been studied within the framework of the Experimental Psycholinguistics, which deals -as it is well known- with language production and comprehension. Taking into account the fact that we must distinguish between slips of the tongue and slips of the pen, on the one hand, and between errors in original documents and in copies, on the other, because they present distinctive features, I have come to the following conclusion: errors in general are not different in other times or in other places. For this reason I consider that the basic processess of language production and comprehension do not change